IN-SILICO MOLECULAR DOCKING STUDIES, SYNTHESIS AND PRELIMINARY PHARMACOLOGICAL EVALUATION OF NEW PYRAZOLINE DERIVATIVES BEARING PYRIDINE RING SCAFFOLDS - MAWLA, MOHAMMED CHASIB; OMAR, TAGREED N-A (International Journal of Applied Pharmaceutics, 2025)
Objective: The primary objective was to study biological activity in vivo, anti-inflammatory activity, antibacterial and antifungal activities, the synthesis of new pyrazoline derivatives 5(a-f) through derivatives bearing heterocyclic scaffolds, molecular docking studies, and the prediction of pharmacokinetic properties of potent molecules by the computational method. Methods: The synthesis of new pyrazoline derivatives 5(a-f) through derivatives bearing heterocyclic scaffolds, characterized via melting point, TLC, and spectral data acquisition (ATR-FTIR-IR, NMR, and mass spectroscopy), and evaluated for in vivo using a rat paw edema model, anti-inflammatory activity with Diclofenac sodium as the standard and in vitro antimicrobial activity against g-positive: Staphylococcus. aureus (S. aureu), Streptococcus. Pyogenes (S. Pyogenes) and g-negative Escherichia. coli (E. coli), Pseudomonas. Aeruginosa (P. aeruginosa)and Candida albicans using the agar-well diffusion method, with amoxicillin and ciprofloxacin as the standard. and ADME for 5(a-f) were evaluated using Ligand Designer from Glide (SchrodingerLLC). Results: The final compound protein of docking (5e and 5d) has the highest docking score (-8.009 and-7.937) in the case of estimating their anti-inflammatory activity, important amino acids in the COX2 enzyme. The final compounds 5a and 5f demonstrated considerable activity from 2 to 5 h. The anti-inflammatory efficacy of the final product was estimated in vivo using a rat paw edema model. They are all important in terms of antibacterial activity. The compounds with the highest docking scores-6.111,-5.964,-5.847,-5.841,-5.272 and-5.093) are 5e,5c,5b,5f,5a and 5d. When compared to DMSO (solvent and control), We used the well diffusion technique to determine the zone of inhibition for the six meticulously synthesized final compounds, then thoroughly tested the new hybrid derivatives for their antimicrobial efficacy against both g-positive and g-negative bacteria. The following fascinating results were obtained: As antimicrobial activity, the high activity all six compounds showed high activity by Staphylococcus. aureus (S. aureu), Streptococcus. Pyogenes (S. Pyogenes): (5b, 5e,5c and 5f);), the high activity all six compounds given by Escherichia. coli (E. coli), Pseudomonas. Aeruginosa (P. aeruginosa) (5a, 5d, 5b, 5c and 5f); give high activity; the others ranging (moderate-inactive). Antifungal activity against Candida albicans, when compared with the drug fluconazole, (5a, 5b, 5c and 5f); the other final compounds were (moderate-inactive). The compounds. Conclusion: The compounds were effectively synthesized, and the findings of the study on their biological efficacy show that the finished compounds contain drug-like properties.